Penguasaan Materi SPLTV Dikaji Dari Karakter Kemandirian Dan Miskonsepsi Bis-VOLKS Pada Siswa MA - Sarry, Noni (Jurnal Pembelajaran Prospektif, 2026)
This study describes the mastery of SPLTV material studied from the independence character and Bis-VOLKS misconceptions in class X students of MA Al-Mustaqim Kubu Raya. This study was motivated by the lack of mastery the material owned by students so that in the process of solving it there were many errors and the results obtained were not optimal. The character of independence is a behavior that must be possessed by every student so that awareness to improve understanding in learning must be accustomed. With the hope that there will be no misconceptions that usually occur in mathematics lessons such as visual, operational, literacy, correlational and spatial misconceptions. The method used in this study is descriptive qualitative. The results of this study are the mastery of SPLTV studied from the independence character and Bis-VOLKS misconceptions which are divided into three categories. In the high category, it is not always directly proportional to the high independence character and experiences spatial misconceptions. In the medium category, it tends not to be directly proportional to the independence character owned and experiences visual misconceptions. As for the low category, it is not directly proportional to the independence character and experiences operational misconceptions, visual and literacy.